Professional Counselors' Interest in Counseling Older Adults. Issue 2 (7th October 2019) - Wagner, Nathaniel J.; Mullen, Patrick R.; Sims, Rachel A.
Abstract : The authors surveyed professional counselors ( N = 956) to examine self‐efficacy in counseling older adults, contact with older adults, and ageism as related to their interest in working with older adults. Higher self‐efficacy, contact, and positive ageism predicted increased interest. These results and implications for counseling older adults are discussed.